The effects of computer‐assisted cognitive rehabilitation on cognitive impairment after stroke: A systematic review and meta‐analysis. Issue 9 (29th August 2021) - Nie, Pingying; Liu, Fang; Lin, Shaohong; Guo, Jiaying; Chen, Xinming; Chen, Sulian; Yu, Liqiang; Lin, Ruhui
Abstract: Objectives: To determine the effectiveness of computer‐assisted cognitive rehabilitation in improving cognitive function in patients with post‐stroke cognitive impairment. Background: In recent years, computer‐assisted cognitive rehabilitation has been accepted as a good substitute or supplement for traditional cognitive rehabilitation. Some clinical randomised controlled trials have been carried out, but no relevant systematic evaluations have been performed. Therefore, we conducted a systematic review of studies involving computer‐assisted cognitive rehabilitation to provide evidence‐based data for its promotion and application. Methods: Nine databases (Cochrane Library, PubMed, Web of Science, Embase, OVID, Wanfang Data, CNKI, VIP and SinoMed databases) were systematically searched. Randomised controlled trials that assessed computer‐assisted cognitive rehabilitation for patients with post‐stroke cognitive impairment were included. Two reviewers appraised the risks of bias through the Cochrane Collaboration's tool and performed the meta‐analysis, including the assessment of heterogeneity. We follow the PRISMA 2020 guidelines. Results: Thirty‐two studies comprising 1837 participants were included. Compared with conventional therapy alone, the addition of computer‐assisted cognitive rehabilitation significantly improved the global cognition of patients, evaluated using the Montreal cognitive assessment, mini‐mental state examination and Loewenstein occupational therapy cognitive assessment ( p < .01 for all tests). The therapy also significantly improved activities of daily living, assessed using the Barthel index, modified Barthel index and functional independence measure ( p < .05 for all tests). Conclusion: Computer‐assisted cognitive rehabilitation significantly improved the cognitive function and activities of daily living of patients with post‐stroke cognitive impairment. Relevance to clinical practice: Computer‐assisted cognitive rehabilitation can be a valuable technique for cognitive rehabilitation after stroke. It is advantageous for improving patient cognition and restoring the overall functional state of patients. Moreover, the research findings can provide suggestions and inspiration for researchers to implement the proposal, which is conducive to the design of more rigorous and high‐quality randomised controlled trials.